Irish English as a World English - Kirk, John (Frontiers in Communication, 2022)
This paper applies a range of models for World Englishes to Irish English, for which data from ICE-corpora, the Handbook of Varieties of English, the Mouton Atlas, eWAVE and GloBwE are used, and to which geo-political, dynamic-model, corpus, statistical, and multi-functional factor analysis approaches are applied. It shows the difficulties of applying top-down models to empirical corpus data and concurs that the gap is ultimately unbridgeable. Nevertheless, in so far as status distinctions can be inferred, this paper also concurs that, as a standardised variety, despite a historical legacy of contact, Irish English is indeed an L1.